As mulheres e a violência simbólica em chove sobre minha infância - Bombassaro, Dayana (2021)
This research aims to analyze situations which reverberates symbolic violence against women, particularly in the family scope. As a research purpose, priority was given to a work of contemporary Brazilian literature, Chove sobre minha infância by Miguel Sanches Neto (2014). The narrative brings in its content the familiar daily experiences, in a rural setting in the countryside of Paraná. From an interdisciplinary theoretical research between psychology and literature, critical and interpretative reading were sought aiming at social and cultural practicing linked to a model’s reproduction based on male dominance and power. It is justified to the problem’s relevance of symbolic violence, including the unnoticed one yet identified on the character’s behavior, on familiar memories and habits consolidated by culture, because everyday women are victims to gender-violence and the contest to contribute to awareness and attitudes changing, man and woman, is urgent. Reflections here presented focused on understand how and under which conditions symbolic violence situations against woman and her place in the family can happen. To this end, familiar relationships, conflicts, lifestyle and workstyle of the characters Nelsa, Carmem Escobar, Carmem Sanches, Gasparina, “painted women”, Miguel Sanches, Sebastião and Zé-Zabé were analyzed. Just like relationships entwining practices beyond time and space, which reproduce symbolic capital legitimizing patriarchal, authoritarians and oppressing believes against women. Resorted to symbolic violence concept’s potential by Pierre Bourdieu, and to Beauvoir, Engelsm, Freyre and Lane’s theoretical support to other analysis among other studious. This study bespoke that in the family relations represented in the work daily symbolic violence situations are established and these refers to behavior’s traces and ideas from patriarchal models, besides finding such practices reproduction quite often, many times silent and or not noticed by a woman. From these female characters, compliance behaviors and social patterns reproduction which meet expectations to family unit were observed, in the middle of symbolic violence situations acclimated in daily actions.